Development of collaborative real-world analysis models for physics teacher candidates. (April 2020) - Firdaus, T; Hamidah, I; Setiawan, W; Kaniawati, I
Abstract: The initial stage of the research has been carried out to develop learning models for physics teacher candidates. The study was conducted by instrument validation which aims to see the standard validity of a learning device. The validation of this instrument consisted of problem-solving test instruments, analytical skills instruments, creativity ability rubrics, student worksheet instruments, and video analysis guide instruments. The method used in this study uses quantitative analysis methods. The results of the study have been made to develop collaborative real-world analysis models to achieve the goals of real-world physics learning. The results of the instrument test show that the instrument is feasible to use and ready to be used as a measurement tool for research.